The Green Catalyst: The Governance–Ownership Nexus in Driving Bank’s Commitment to Green Loans (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Global awareness of the climate crisis has prompted the banking sector to contribute to the transition towards a low-carbon economy, notably through green financing. This study examines the influence of governance and ownership structure on green loan commitments. Based on agency theory, the research tests hypotheses using secondary data from 72 commercial banks listed on the Indonesia Stock Exchange between 2017 and 2024, including both State-Owned Banks (Bank Persero) and National Private Commercial Banks. The results indicate that CEO duality and gender diversity have a significant negative impact on green financing, while board financial expertise has a positive effect. Most interactions between ownership structure and governance mechanisms with key variables are not significant. however, the interaction between board expertise and institutional ownership shows a significant negative effect, suggesting potential conflicts of interest or differing priorities in advancing the green agenda. This research contributes to the sustainable finance literature and provides practical implications for regulators, bank management, and investors in strengthening green loan strategies.
Keywords: Corporate Governance; Ownership; Green Loans